Expanded polyQ aggregates interact with sarco-endoplasmic reticulum calcium ATPase and Drosophila inhibitor of apoptosis protein1 to regulate polyQ mediated neurodegeneration in Drosophila. - Maurya, C.K.; Tapadia, M.G. (Molecular and Cellular Neurosciences, 2023)
Polyglutamine (polyQ) induced neurodegeneration is one of the leading causes of progressive neurodegenerative disorders characterized clinically by deteriorating movement defects, psychiatric disability, and dementia. Calcium [Ca[2+]] homeostasis, which is essential for the functioning of neuronal cells, is disrupted under these pathological conditions. In this paper, we simulated Huntington's disease phenotype in the neuronal cells of the Drosophila eye and identified [Ca[2+]] pump, sarco-endoplasmic reticulum calcium ATPase (SERCA), as one of the genetic modifiers of the neurodegenerative phenotype. This paper shows genetic and molecular interaction between polyglutamine (polyQ) aggregates, SERCA and DIAP1. We present evidence that polyQ aggregates interact with SERCA and alter its dynamics, resulting in a decrease in cytosolic [Ca[2+]] and an increase in ER [Ca[2+]], and thus toxicity. Downregulating SERCA lowers the enhanced calcium levels in the ER and rescues, morphological and functional defects caused due to expanded polyQ repeats. Cell proliferation markers such as Yorkie (Yki), Scalloped (Sd), and phosphatidylinositol 3 kinases/protein kinase B (PI3K/Akt), also respond to varying levels of calcium due to genetic manipulations, adding to the amelioration of degeneration. These results imply that neurodegeneration due to expanded polyQ repeats is sensitive to SERCA activity, and its manipulation can be an important step toward its therapeutic measures.